PENGARUH MOTIVASI DAN EMPLOYEE ENGAGEMENT TERHADAP KOMITMEN ORGANISASI SERTA ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi pada Bank Jateng Purbalingga) - Berlina Mahardika Vita; Widhy Setyowati (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study purpose to analyze the effect of motivation and employee engagement on organizational commitment and OCB, as well as the mediating effect of commitment on the effect of motivation and employee engagement on OCB of Bank Jateng Purbalingga employees. The technique of determining the sample is saturated sampling so that all the population becomes a sample of 44 people. The analytical tool used is Partial Least Square with t test and mediation test using VAF method. The results showed that there was an influence of motivation and employee engagement on organizational commitment and OCB, and commitment to mediate the influence of motivation and employee engagement on OCB for Bank Jateng Purbalingga employees with an overall significance value of less than 0.05.